2012
DOI: 10.1111/1751-2980.12001
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial embolization followed by octreotide and celecoxib synergistically prolongs survival of rabbits with hepatic VX2 allografts

Abstract: TAE followed by the long-term administration of octreotide and celecoxib can synergistically prolong the survival of rabbits with hepatic VX2 allografts by inhibiting potential neoangiogenesis, tumor growth and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…Previous studies have demonstrated that the majority of rabbits underwent metastasis ~40 days after tumor implantation (8,14). Distal metastasis and abdominal implantation occurring at a late stage of liver carcinoma were usually accompanied by either intrahepatic metastasis or large primary implantation foci (8). Conversely, in the present study, rabbits in group A, whose peritoneum was scattered with nodules, possessed hepatic allograft diameters of <5 cm at 14 days after tumor implantation, without concomitant intrahepatic or lung metastasis.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Previous studies have demonstrated that the majority of rabbits underwent metastasis ~40 days after tumor implantation (8,14). Distal metastasis and abdominal implantation occurring at a late stage of liver carcinoma were usually accompanied by either intrahepatic metastasis or large primary implantation foci (8). Conversely, in the present study, rabbits in group A, whose peritoneum was scattered with nodules, possessed hepatic allograft diameters of <5 cm at 14 days after tumor implantation, without concomitant intrahepatic or lung metastasis.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous studies have demonstrated that the majority of rabbits underwent metastasis ~40 days after tumor implantation (8,14). Distal metastasis and abdominal implantation occurring at a late stage of liver carcinoma were usually accompanied by either intrahepatic metastasis or large primary implantation foci (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of VX2 hepatic allografts in rabbits, TAE procedure and experimental grouping were the same as in our previous study (14). Briefly, 72 rabbits were randomly assigned into four groups.…”
Section: Methodsmentioning
confidence: 99%
“…Somatostatin (SST) is one of the regulatory peptides for arresting the growth of HCC and the overexpression of SST receptors has also been identified in HCC (12). Our previous studies demonstrated that a combination of a COX-2 inhibitor with an SST analogue not only had an enhanced anti-proliferative effect and suppressed the metastasis of HCC in nude mice (13) but also prolonged the survival of rabbits with liver cancer that received TAE (14). …”
Section: Introductionmentioning
confidence: 99%